Visiting George and Patricia Kamp In Sun Valley, Nevada - Watkins, Howard::::::::: (1983)
Howard Watkins, Christine Watkins, Robin Watkins held on to of railing, Patricia Kamp, George Kamp and Adam Watkins on front wooden porch deck